2004
DOI: 10.1002/jat.952
|View full text |Cite
|
Sign up to set email alerts
|

l‐Arginine ameliorates oxidative stress in alloxan‐induced experimental diabetes mellitus

Abstract: Oxidative stress occurs in diabetic patients and experimental models of diabetes. The ability of l-arginine to ameliorate the oxidative stress and metabolic changes after treatment with alloxan was investigated in rats. Adult male rats were injected intraperitoneally with 100 mg kg(-1) of alloxan to produce experimental oxidative stress characteristic of diabetes mellitus. Hyperglycaemia and hypercholesterolaemia were observed in serum after 7 days of alloxan treatment. This was associated with a depression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
40
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 43 publications
9
40
1
Order By: Relevance
“…It seems that there is an association between radiationinduced oxidative stress and elevated levels of lipid fractions and LDL (Onody et al, 2003). This association is similarly observed in other conditions characterized by increased oxidative stress (El-Missiry et al, 2004;ZwirskaKorczala et al, 2003). Therefore, this study suggests that additional experiments will be performed taking into consideration the levels of LDL, high density lipoprotein (HDL), lipid peroxidation through MDA, GSH content, catalase (CAT) activity and DNA content.…”
Section: Resultsmentioning
confidence: 68%
“…It seems that there is an association between radiationinduced oxidative stress and elevated levels of lipid fractions and LDL (Onody et al, 2003). This association is similarly observed in other conditions characterized by increased oxidative stress (El-Missiry et al, 2004;ZwirskaKorczala et al, 2003). Therefore, this study suggests that additional experiments will be performed taking into consideration the levels of LDL, high density lipoprotein (HDL), lipid peroxidation through MDA, GSH content, catalase (CAT) activity and DNA content.…”
Section: Resultsmentioning
confidence: 68%
“…Citrulline is the precursor of Arg [133]. Studies suggested that Arg can scavenge ROS in rat hearts [134] and abrogate oxidative stress in experimental mice [135,136] and patient [137]. Fujita and Yanaga reported that the levels of Ala, Cit and Pro are 0.258-0.327 mM, 0.019-0.056 mM and 0.124-0.141 mM in human plasma, respectively [12].…”
Section: Effects Of the Combination Of Ala Cit And Pro On • Oh-inducmentioning
confidence: 99%
“…As an essential nutrient, it plays an important role in cell division, the healing of wounds, removing ammonia from the body, immune function such as stimulating T-and natural killer cell activity and influencing pro-inflammatory cytokine level, and the release of hormones [1][2][3]. Many studies have been shown that Arg has dual effects as toxic or protective effects against toxicity in the cells [4][5][6]. Arg serves also as an intermediary in the urea cycle and as a precursor for protein, polyamine, creatine and nitric oxide (NO) biosynthesis which is involved in the physiological control of different tissue at lower levels.…”
Section: Introductionmentioning
confidence: 99%